Sox21 inhibits glioma progression in vivo by forming complexes with Sox2 and stimulating aberrant differentiation. Issue 6 (4th April 2013) - Caglayan, Demet; Lundin, Erika; Kastemar, Marianne; Westermark, Bengt; Ferletta, Maria
<x xml:space="preserve">Abstract</x> Sox2 is a transcription factor in neural stem cells and keeps the cells immature and proliferative. Sox2 is expressed in primary human glioma such as glioblastoma multiforme (GBM), primary glioma cells and glioma cell lines and is implicated in signaling pathways in glioma connected to malignancy. Sox21, the counteracting partner of Sox2, has the same expression pattern as Sox2 in glioma but in general induces opposite effects. In this study, Sox21 was overexpressed by using a tetracycline‐regulated expression system (tet‐on) in glioma cells. The glioma cells were injected subcutaneously into immunodeficient mice. The control tumors were highly proliferative, contained microvascular proliferation and large necrotic areas typical of human GBM. Induction of Sox21 in the tumor cells resulted in a significant smaller tumor size, and the effect correlated with the onset of treatment, where earlier treatment gave smaller tumors. Mice injected with glioma cells orthotopically into the brain survived significantly longer when Sox21 expression was induced. Tumors originating from glioma cells with an induced expression of Sox21 exhibited an increased formation of Sox2:Sox21 complexes and an upregulation of S100β, CNPase and Tuj1. Sox21 appears to decrease the stem‐like cell properties of the tumor cells and initiate aberrant differentiation of glioma cells in vivo. Taken together our results indicate that Sox21 can function as a tumor suppressor during gliomagenesis mediated by a shift in the balance between Sox2 and Sox21. The wide distribution of Sox2 and Sox21 in GBM makes the Sox2/Sox21 axis a very interesting target for novel therapy of gliomas.